(untitled) (Clinics, 2008)
OBJECTIVE: This study analyzes the reliability of the PHEEM questionnaire translated into Portuguese. We present the results of PHEEM following distribution to doctors in three different medical residency programs at a university hospital in Brazil. INTRODUCTION: Efforts to understand environmental factors that foster effective learning resulted in the development of a questionnaire to measure medical residents' perceptions of the level of autonomy, teaching quality and social support in their programs. METHODS: The questionnaire was translated using the modified Brislin back-translation technique. Cronbach's alpha test was used to ensure good reliability and ANOVA was used to compare PHEEM results among residents from the Surgery, Anesthesiology and Internal Medicine departments. The Kappa coefficient was used as a measure of agreement, and factor analysis was employed to evaluate the construct strength of the three domains suggested by the original PHEEM questionnaire. RESULTS: The PHEEM survey was completed by 306 medical residents and the resulting Cronbach's alpha was 0.899. The weighted Kappa was showed excellent reliability. Autonomy was rated most highly by Internal Medicine residents (63.7% ± 13.6%). Teaching was rated highest in Anesthesiology (66.7% ± 15.4%). Residents across the three areas had similar perceptions of social support (59.0% ± 13.3% for Surgery; 60.5% ± 13.6% for Internal Medicine; 61.4% ± 14.4% for Anesthesiology). Factor analysis suggested that nine factors explained 58.9% of the variance. CONCLUSIONS: This study indicates that PHEEM is a reliable instrument for measuring the quality of medical residency programs at a Brazilian teaching hospital. The results suggest that quality of teaching was the best indicator of overall response to the questionnaire.